2012
DOI: 10.1111/j.1943-278x.2011.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychache and Suicide Ideation among Men Who Are Homeless: A Test of Shneidman’s Model

Abstract: Suicide ideation among the homeless is 10 times more common than in the general population. Cognitive theories of depression and hopelessness propose to explain suicidality; however, as yet, none of these fully account for the phenomenon. Shneidman has suggested a theory of psychache or unbearable psychological pain to explain suicidality. This theory has found support among low-risk populations but has not been extensively tested within a high-risk population. The current research assessed the utility of psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 37 publications
7
62
1
4
Order By: Relevance
“…Psychache had stronger power in predicting suicidal ideation and suicide attempt than life satisfaction, as evidenced by its larger standardised regression coefficients. This result is in line with the finding from other studies testing Shneidman's theory with samples of general population41 and special groups as offenders,33 42 homeless people20 and patients with mental illness 43. The result supports Shneidman's view that psychache is a fundamentally important predictor for suicidal behaviour.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Psychache had stronger power in predicting suicidal ideation and suicide attempt than life satisfaction, as evidenced by its larger standardised regression coefficients. This result is in line with the finding from other studies testing Shneidman's theory with samples of general population41 and special groups as offenders,33 42 homeless people20 and patients with mental illness 43. The result supports Shneidman's view that psychache is a fundamentally important predictor for suicidal behaviour.…”
Section: Discussionsupporting
confidence: 90%
“…It is associated with many psychological suicidogenic factors such as depression and hopelessness, but is also conceptually distinct from these factors 18 19. Evidence has shown that psychache is a significant and unique predictor for various suicide criteria, including suicidal ideation and suicide attempt, even after being controlled for effects of depression and hopelessness 18 20 21. According to Shneidman,16 17 psychache is fundamentally linked with suicide on its own, whereas other psychological factors and affective states (eg, depression, hopelessness, etc) are relevant to suicide only insofar as they lead to psychache.…”
Section: Introductionmentioning
confidence: 99%
“…Initial support for psychache as a factor in suicide is strong. Psychache has been shown to be a significant predictor of suicide ideation and attempts (Flynn & Holden, 2007;Holden, Mehta, Cunningham et al, 2001;Mills, Green, & Reddon, 2005;Patterson & Holden, 2012;Pereira, Kroner, Holden et al, 2010;Troister & Holden, 2010a;Troister & Holden, 2010b). Research has also supported Shneidman's assertion that the relationship of other factors with suicide is mediated by psychache, and that psychache and suicide ideation co-vary over time (DeLisle & Holden, 2009;Troister & Holden, 2012 Troister & Holden, 2012).…”
Section: Psychological Pain Theoriesmentioning
confidence: 86%
“…11 Depresyon ile intihar düşüncesi, intihar hazırlığı, geçmiş intihar girişimleri ve yaşam boyu intihar girişimi sayısı arasındaki bağlantıyı psikolojik acı varlığının sağladığı gösterilmiştir. 12,13 Psikolojik acı (psikolojik ağrı, mental ağrı) terimi ortaya çıktıktan sonra bu duygunun niteliğini ve niceliğini ölçme amacıyla ilk olarak Shneidman tarafından Psikolojik Acı Değerlendirme Ölçeği (PPAS) geliştirilmiştir. 14 Psychache Scale (Psikolojik Acı Ölçeği) ise Holden ve arkadaşları tarafından geliştirilen 13 maddelik bir özbildirim ölçeğidir.…”
unclassified